Surface characteristics and CO2 adsorption capacities of acid-activated zeolite 13X prepared from palm oil mill fly ash. (1st April 2017) - Kongnoo, Aroon; Tontisirin, Supak; Worathanakul, Patcharin; Phalakornkule, Chantaraporn
Graphical abstract: Highlights: Zeolite 13X was synthesized from palm fly ash by alkaline fusion. An optimal fusion temperature was 600 °C for 60 min. Acid activation with 2 M HCl increased micropore surface area from 353 to 450 m 2 /g. Acid activation (6 M HCl/4 h) increased pore volume from 0.294 to 0.920 cm 3 /g. CO2 adsorption on the zeolite depended on pore volume more than surface area. Abstract: Zeolite 13X was synthesized from palm oil mill fly ash (POMFA) using an alkaline fusion method. A zeolite 13X yield of 85% was obtained at a mass ratio of NaOH/(SiO2 and Al2 O3 precursors) of 1.6, a fusion temperature of 600 °C and a fusion time of 60 min. Acid activation was performed on the zeolite 13X product in order to enhance its CO2 adsorption capacity. Acid activation with 4–8 M HCl for 4 h produced a marked increase in the mesopore and total pore volumes of the zeolite 13X. This increased mesopore volume resulted in CO2 adsorption capacities of the acid-activated zeolite 13X at 6 M HCl for 4 h that were 22% higher than those of the unactivated zeolite 13X and 11% higher than those of the commercial zeolite 13X. The CO2 adsorption capacity obtained was 6.42 mol CO2 /kg at a pressure of 403 kPa and a temperature of 32 °C.